Reducing the Health Burden of HPV Infection Through Vaccination (Hindawi Limited, 2006)
Human papillomavirus (HPV), a sexually transmitted infection and the etiologic cause of genital warts and cervical cancer, is highly prevalent in sexually active men and women. Although cervical screening procedures have significantly reduced the disease burden associated with HPV infection, they are expensive and abnormal results cause significant emotional distress. Therefore, prevention may be an effective strategy for reducing the economic, psychosocial, and disease burden of HPV infection. Multivalent vaccines are now in clinical development. A bivalent vaccine that protects against HPV 16 and 18, and a quadrivalent vaccine which protects against HPV types 6, 11, 16, and 18, have been shown to significantly reduce the occurrence of incident and persistent HPV infections in phase 2 clinical trials; phase 3 trials are currently underway. HPV vaccines will be most effective when administered prior to initiation of sexual activity, and vaccination campaigns should aggressively target preadolescent and adolescent populations.